2018
DOI: 10.3390/ijms19051335
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-Mangostin Provides Protective Effects against Acetaminophen-Induced Hepatotoxicity in Mice via Akt/mTOR-Mediated Inhibition of Autophagy and Apoptosis

Abstract: Acetaminophen overdose-induced hepatotoxicity is the most common cause of acute liver failure in many countries. Previously, alpha-mangostin (α-MG) has been confirmed to exert protective effects on a variety of liver injuries, but the protective effect on acetaminophen-induced acute liver injury (ALI) remains largely unknown. This work investigated the regulatory effect and underlying cellular mechanisms of α-MG action to attenuate acetaminophen-induced hepatotoxicity in mice. The increased serum aminotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…The results revealed that dioscin induced autophagy against HCC in vivo and in vitro. The signal of Akt/mTOR is important in regulating intracellular homeostasis, and it is reported that activation of Akt/mTOR signal is essential in autophagy (Yan et al, ). Interestingly, recent studies have highlighted that TIGAR knockdown can enhance epriubicin‐induced autophagy by inhibiting mTOR pathway, suggesting the protective effect of autophagy on the survival of cancer cells when TIGAR is knocked down (Kumar, Iqbal, Singh, & Bamezai, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that dioscin induced autophagy against HCC in vivo and in vitro. The signal of Akt/mTOR is important in regulating intracellular homeostasis, and it is reported that activation of Akt/mTOR signal is essential in autophagy (Yan et al, ). Interestingly, recent studies have highlighted that TIGAR knockdown can enhance epriubicin‐induced autophagy by inhibiting mTOR pathway, suggesting the protective effect of autophagy on the survival of cancer cells when TIGAR is knocked down (Kumar, Iqbal, Singh, & Bamezai, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that excessive ROS induced by APAP results in phosphorylation of JNK, which further amplifies mitochondria oxidative stress [23]. Moreover, the pro-apoptotic protein Bax, which belongs to the Bcl-2 family of proteins, is highly expressed exposed to an APAP overdose [24,25,26]. The pathophysiological importance of Bax in APAP hepatotoxicity has been shown by the temporary inhibition of nuclear DNA fragmentation and delayed cell death in Bax-deficient mice [27].…”
Section: Resultsmentioning
confidence: 99%
“…Bax is a pro-apoptotic Bcl-2 family member located predominantly in the cytosol. Exposed to an APAP overdose, it is highly expressed [24,25,26]. It has been reported that APAP-induced mitochondrial Bax expression was attenuated by the inhibition of JNK activation [11].…”
Section: Discussionmentioning
confidence: 99%
“…The desiccative mangosteen pericarp powder (20 g) was extracted with 200 mL of 85% ethanol for 5 min twice by the smashing tissue extraction (STE) method. 4 The purity of α-MG is more than 98%.…”
Section: Methodsmentioning
confidence: 99%